2022
DOI: 10.1002/nvsm.1762
|View full text |Cite
|
Sign up to set email alerts
|

Relational care in communication as the basis of nonprofit fundraising: Theorizing professional ethics based in stewardship and ethics of care

Abstract: At its core, fundraising is relationship building. Therefore, ethical fundraising requires cultivating genuine, care‐based relationships between various stakeholders by considering relational goals and communicative practices. We advance an ethics of care‐oriented approach toward fundraising based in nurturing authentic relationships with multiple organizational stakeholders, including donors, employees, beneficiaries, and volunteers. Drawing upon ethics of care and stewardship scholarship based in public rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 85 publications
(202 reference statements)
0
3
0
Order By: Relevance
“…In addition, studies address questions about how to improve NPOs' fundraising outcomes (Kim, Gupta, & Lee, 2021; Nageswarakurukkal et al, 2020; Yoo & Drumwright, 2018; Zheng, 2020). Within this field, other studies address how to build and maintain relationships between donors and NPOs (Arnett et al, 2003; Boenigk & Scherhag, 2014; Madden et al, 2022). Key influence factors appear to include trust, satisfaction, and commitment (Waters, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, studies address questions about how to improve NPOs' fundraising outcomes (Kim, Gupta, & Lee, 2021; Nageswarakurukkal et al, 2020; Yoo & Drumwright, 2018; Zheng, 2020). Within this field, other studies address how to build and maintain relationships between donors and NPOs (Arnett et al, 2003; Boenigk & Scherhag, 2014; Madden et al, 2022). Key influence factors appear to include trust, satisfaction, and commitment (Waters, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…While stewardship has demonstrated its importance in myriad sectors of society, perhaps there is no area where it has more consistently illustrated its utility than in the organization‐donor relationship (e.g., Harrison, 2019; Madden et al, 2022; Remund & McKeever, 2018; Worley & Little, 2002). For example, scholars have found that stewardship is imperative for sustaining relationships with major donors (Waters, 2009b), that it can help to predict major donations versus annual gifts (Waters, 2011a) and that it is an antecedent to desirable outcomes such as donor loyalty (Pressgrove & McKeever, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It implies that the corporation should be responsible and attentive, recognize the stakeholders’ needs, and be competent to respond to them. Caring practices and values should consequently encompass trust building, mutual respect and concern, responsiveness to needs, mutually beneficial relationships, human flourishing, and communication within the organization ( Formentin and Bortree, 2019 ; Madden et al, 2022 ; Lemon and Boman, 2022 ). And all this can be done through the various CSR actions, but specially through corporate donations, which will improve the quality of life of the various stakeholders and concretely will solve social problems as Inditex had done during the pandemic as it will be analyzed as follows.…”
Section: Theoretical Backgroundmentioning
confidence: 99%